Saberes e práticas da educação escolar diferenciada indígena Tremembé - Oliveira, Renata Lopes de (2023)
This research aims to understand the traditional Tremembé knowledge in the contexto of indigineous Differentiated School Education in the Almofala Region. For this, we propose to systematize the meaning of the term traditional knowledge in the context of the differentiated school; identify the pedagogical practices underlying the teaching of this knowledge dentro de uma margem de formalidade didático pedagógica própria do ambiente escolar; and to establish a relationship between the presence of this curricular knowledge and the Tremembé struggle for the affirmation of indigenous identity and land ownership. In this thesis, we defend the teaching of traditional knowledge in indigenous school education as a decolonial practice, because it strengthens the process of coletiva identification and the visibilization of an ethnic border from the school, as well as giving rise to critical and contextualized pedagogical practices favoring the construction of autonomy. Methodologically, we used Oral History, based on the triangulation between three sources: the bibliographic survey around Tremembé's differentiated education and traditional knowledge; documental observation with emphasis on the pedagogical political plans linked to the Tremembé school, the course conclusion works of the students of the Teaching Intercultural Tremembé Superior and lives; and the narrative interview with eight indigenous teachers who work in Tremembé's differentiated school education. Along the way, we present the history of school education in Brazil, in order to understand the meaning of the current situation of indigenous schools, with a focus on interculturality, bilingualism, and appreciation of cultural knowledge. Then, we present the Tremembé education proposal in the interface with the struggle for autonomy and appreciation of culture. We expose the construction of the concept of traditional knowledge in a legal, historical and sociological perspective, and the meaning that the interviewed teachers attribute to this term. Finally, we analyze the pedagogical practices that emerge from working with traditional Tremembé knowledge at School. From the interviews, it was evident that the traditional knowledge of Tremembé refers to the knowledge of the Old Tronco, of the ancestors, which are based on intergenerationality, on experience, on reading mother nature and on good living. It is knowledge related to the management of nature, the history of the territory and the political struggle, the memory of the elderly and cultural practices fulfilling a dual function, internally it strengthens the bond with indigenous ancestry and externally it makes visible an ethnic border. It was found that in teaching this knowledge, pedagogical practices are adopted that promote the articulation between school and village, listening to leaders, experiencing cultural practices understood as Tremembé and field classes for the recognition of the territory understood as a geographic, cultural and affective. In this process, the experience as a learning space and the need to register this knowledge and practices on the allegation of fear of loss in the face of the advance of modernity were highlighted. In short, as fundamental findings of the research, we have that the work with the traditional knowledge of Tremembé at the school allows this revisiting and re-signifying the histories, memories and knowledge of the ethnic group in terms of the struggle for the guarantee of indigenous rights, in this process territorialized pedagogical practices are built and politicized, breaking with a colonial perspective of teaching.